From Animals to Animats 14 14th International Conference on Simulation of Adaptive Behavior, SAB 2016, Aberystwyth, UK, August 23-26, 2016, Proceedings - Tuci, Elio; Giagkos, Alexandros; Wilson, Myra; Hallam, John (Lecture Notes in Artificial Intelligence,, 2016)
This book constitutes the proceedings of the 14th International Conference on Simulation of Adaptive Behavior, SAB 2016, held in Aberystwyth, UK, in August 2016. The 31 papers presented in this volume were carefully reviewed and selected from 45 submissions. They cover the main areas in animat research, including the animat approach and methodology, perception and motor control, learning and adaptation, evolution, and collective and social behavior.